2002
DOI: 10.1200/jco.2002.20.1.282
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Ischemic Stroke After Radiotherapy on the Neck in Patients Younger Than 60 Years

Abstract: This is the first study to demonstrate an increased risk of stroke after RT on the neck. During medical follow-up, preventive measures should be taken to reduce the impact of the risk factors for cerebrovascular disease, to decrease stroke in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
155
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 234 publications
(176 citation statements)
references
References 23 publications
9
155
0
12
Order By: Relevance
“…Relative quantities of alcohol consumption were not consistently available across participants. Although the number of persons included in this analysis was small, the annual CVE rate was significant, consistent with previous neck RT reports 3, 4…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Relative quantities of alcohol consumption were not consistently available across participants. Although the number of persons included in this analysis was small, the annual CVE rate was significant, consistent with previous neck RT reports 3, 4…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, in an analysis of >50 000 RT‐treated HNCA patients, traditional risk factors (hypertension and diabetes mellitus) were observed in only 30% of stroke events 22. Consequently, there are likely other risk factors that may at least partially explain the >500% increased risk of stroke events faced by HNCA patients treated with RT 3, 4. In this study, we found that HPV status was predictive of stroke and TIA following RT, even after adjustment for traditional risk factors and RT dose.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations